Religious Counseling with Respectful Based Assessment to Strengthen the Religious Moderation Behavior of Students in Islamic Boarding Schools (Case Study at Al Insaniyyah Islamic Boarding School) - Algifahmy, Ayu Faiza; Robby, Fadli; Wibowo, Eko Setiyo Ary; Arip Febrianto; Rosa Maulida Khasanah (Universitas PGRI Yogyakarta, 2026)
Islamic boarding school students play a crucial role in promoting religious moderation among Generation Z, who are at risk of extremism due to misleading information. The Respect-Based Assessment approach in religious counseling provides a solution by focusing on respect for individual values and understanding students' perspectives to foster moderate and tolerant attitudes. This qualitative research, using field research methods such as interviews and observations, aims to explore how religious counseling helps build religious moderation among students. The study found that students who participated in this counseling experienced increased self-awareness, tolerance for differences, and social engagement. Clerics, acting as counselors, contribute to this process through education, dialogue, and serving as role models, which further encourages moderate behavior among students. Efforts include enhancing Generation Z's understanding of diversity, providing guidance during identity crises, promoting intergenerational dialogue, and addressing stigma and contemporary challenges through religious counseling. Keywords: religious counseling, respect-based assessment, religious moderation